Effect of Compensation, Motivation and Work Discipline on Employee Performance in Setigi Tourism Sekapuk Ujungpangkah - Bangkit Feby Finansyah; Maulidyah Amalina Rizqi (Indonesian Vocational Research Journal, 2022)
Human resource management is the relationship and role of human Learn about a field in organizational management in a company. Humans in every activity of the organization have an important and play an active role, namely as a designer, as an implementer, and as a determinant in realizing organizational goals. The purpose of this study is to partially analyze the effect of compensation, related to motivation and work discipline on the performance of employees in the tourism sector in Setigi Village, Sekapuk Ujungpangkah District, Gresik Regency. For the method, this research used by the researcher is a quantitative method then for the analysis technique used by the researcher is multiple linear regression analysis with SPSS version 22 program For the sample used in this study amounted to 50 respondents Collecting data using a Likert scale questionnaire The results of this study are showing that the compensation variable with a significance value of 0.030 while the motivation variable with a significance value of 0.088 and work discipline with the highest significance value of 0.683. It also shows that the value of the three independent variables.is greater than 0.05. Therefore, it can be concluded that all of these variables have no significant effect on the performance of employees in the tourism sector in Setigi Village, Sekapuk Subdistrict, Ujungpangkah, Gresik Regency.